A Case Report of Psychogenic Erectile Dysfunction with Ego Dystonic Sexual Disorientation: Is Still Relevant to Treat? - Geraldo Laurus; Cennikon Pakpahan; William William; Raditya Ibrahim (Indonesian Andrology and Biomedical Journal, 2023)
Background: Converting Ego-dystonic homosexual to heterosexual is still controversial. homosexuals are encouraged to be accepted and do not require conversion. Currently, many cases of homosexuals are required to accept their identity and do not require conversion. However, there are times when patients want to be heterosexual and experience sexual dysfunction because of this orientation. Then, how a medical professional deal with such a case especially in the era of ease of information and technology? Choose to demand that the patient accept their sexual orientation or help the patient to become heterosexual. Objective: Here we present the case of a man, 44 years old, with a psychogenic erection with ego-dystonic homosexual disorientation, along with a review of the literature related to the case. Method: A case report with literature review Case/Result: We report 44-year-old man who has been married for six years complains of difficulty and decreased erection for 5.5 years. This man had a history of sexual intercourse with men during college but decided to become a heterosexual man and married his current wife. For the first six months, the patient performed oral sex with his wife. Then afterwards, the patient has difficulty getting an erection and even fails. The patient feels guilty toward his wife until their relationship becomes a crisis. The patient wants to commit to being a heterosexual man. So, the patient came to the andrology clinic for therapy. We applied intersystemic assessment approach to the patient. There is progress in the patient’s condition until now. Conclusion: Many experts say that homosexuality should be accepted and should not be converted. But in the end, the choice is returned to the patient, whether to choose to convert or not. Physicians only need to support the patient's therapy and choices so that he does not experience any mental disorders that ultimately endanger his life. Keywords: , , , ,